Occurence of Powdery Mildew Caused by Podosphaera xanthii on Vigna nakashimae in Korea - Kyung-Gu Min; Tae-Min Park; Youn-Jin Park; Myoung-Jun Jang (Research in Plant Disease, 2022)
In October 2022, common Asian cowpea (Vigna nakashimae) powdery mildew disease was investigated at Yesan-gun, Chungcheongnam-do, Korea (36°40’12.7′ N,126°51’36.4′ E). The disease mainly occurred on the front of the leaves, and weak powdery mildew disease occurred on the back side of leaf. The chasmothecia was identified on the back side of the leaf. Analysis of the internal transcribed spacer rDNA sequence and 28S large subunit sequence, along with the morphological characteristics of the anamorph and teleomorph of the causal fungus identified as Podosphaera xanthii. This is the first time in Korea to report common Asian cowpea (Vigna nakashimae) powdery mildew disease caused by Podospaera xanthii.